Analisis Sifat Kimia Air Tanah Sumur Dangkal Pada Tanah Berkapur (Desa Gamping Kecamatan Campurdarat Kabupaten Tulungagung) - Emma Yuliani; Dea Rozan Aqil Pradana (Fakultas Teknik, Universitas Brawijaya, 2019)
Groundwater is one of the many alternative water sources that have a large and very good quantity and quality. An important factor that must be considered in groundwater management is the analysis of its chemical characteristics. These chemical characteristics will have a large impact on objects that receive and consume ground water regularly. The purpose of this study was to determine the effect of the risk of the object receiving and knowing the chemical characteristics of groundwater in the study location. To find out the effect of the occurrence of risk on the research location, use the equation recommended by the EPA (Environmental Protection Agency). Analysis of the chemical characteristics of groundwater was carried out using the Pie Chart Method, and the Kurlov Method. From the results of research conducted in Gamping Village, Campurdarat District, Tulungagung Regency, it is known that the groundwater in the study site has health risk factors and is dominated by anion bicarbonate (HCO3 - ), and kation calcium, sodium.